Effect of water stress on nitrogen fixation and nodule structure of common bean - Ramos, Maria Lucrecia Gerosa; Parsons, Richard; Sprent, Janet Irene; James, Euan Kelvin (Pesquisa Agropecuaria Brasileira, 2003)
The aim of this work was to investigate the effect of water stress on N2 fixation and nodule structure of two common bean (Phaseolus vulgaris L.) cultivars Carioca and EMGOPA-201. Plants were harvested after five and eight days of water stress. Carioca had lower nodule dry weight on both water stress periods; shoot dry weight was lower at five days water stress and did not differ from control after eight days stress. Both cultivars had lower nitrogenase activity than control after five and eight days water stress. For both cultivars, after eight days stress bacteroid membranes were damaged. Carioca presented more pronounced damage to infected tissue, with host cell vacuolation and loss of the peribacteroid membrane at five days after stress; at eight days after stress, there was degradation of cytoplasm host cells and senescence of bacteroids, with their release into intercellular spaces. Intensity of immunogold-labeling of intercellular cortical glycoprotein with the monoclonal antibodies MAC 236/265 was different for both cultivars.
Keywords: Phaseolus vulgaris; nitrogenase; leaf water potential; nodulation